The Influence of Digital Media on Aggression in Indonesian Children : A Systematic Review - Ruth Floren Armiwita Septapani Berutu (International Journal of Humanities and Social Sciences Reviews, 2024)
The effects of digital media on children are unfortunate given how much of an impact they have on the world. Children who are exposed to violent media may act aggressively both physically and verbally. Either right away after media exposure or months and possibly years later, the behavior takes place. Children will act according to what they see for most of their lives, which means how much time they spend watching content that endangers their lives, such as hateful material about other children, peers, adults, or animals, inciting racism, or posting or disturbing images. Children become aggressive due to violent television shows. “Television can harm children by making them passive learners, distracting them from doing homework, teaching them models of violent aggression, and presenting them with an unrealistic world view.” A qualitative approach with a PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) 2020 - based systematic review method is used in this study. The sample criteria used were derived from articles or journals that investigated the impact of media on aggressive behaviour in children aged 0-18 years. Children who spend 2-5 hours per day watching television can become aggressive. Violence-inducing television shows and online games, if consumed daily, will gradually lead to aggressive behavior, both verbally and physically. Social media will teach you to be verbally aggressive in the online world. Parents and teachers play an important role in children's development. Parents are expected to accompany their children to all home activities, while teachers are encouraged to educate students on the dangers of excessive digital media use.